Understanding personal agency through metaphor, or Why academic writing is (not) like a roller-coaster ride - Karsten, Andrea (Frontiers in Language Sciences, 2025)
Building on and methodologically extending conceptual metaphor theory, the article examines how personal agency as a discursively produced sociopsychological phenomenon can be studied in elicited metaphors through a discourse-analytical approach. More concretely, the study illustrates how early-career researchers experience and express their agency in research writing through personal metaphors of academic writing such as riding a roller coaster or baking a wedding cake. A two-step discursive analysis adapts Hopper and Thompson's multidimensional approach to linguistic transitivity to study agency in language. The analytical approach involves both an in-depth parametrized analysis of all metaphors in the sample and a qualitative cross-analysis of the data. The results show that the participants' metaphors reflect both nuanced personal experiences and cultural expectations of academic writing, the writer, and the text. This emphasizes that research writing is not only a highly subjective practice but also one that is socially and culturally influenced. The article argues that research on agency thus needs elaborate methodological tools to trace discursive and sociopsychological trajectories of complex socio-cognitive practices like academic writing. This has implications not only for the nexus of research writing, identity, and academic enculturation but also for other fields focusing on agency in language.